Structural Elaboration of a Natural Product: Identification of 3, 3′‐Diindolylmethane Aminophosphonate and Urea Derivatives as Potent Anticancer Agents. Issue 11 (28th August 2013) - Kandekar, Somnath; Preet, Ranjan; Kashyap, Maneesh; M. U., Renu Prasad; Mohapatra, Purusottam; Das, Dipon; Satapathy, Shakti Ranjan; Siddharth, Sumit; Jain, Vaibhav; Choudhuri, Maitrayee; Kundu, Chanakya N.; Guchhait, Sankar K.; et al.
Abstract An approach involving rational structural elaboration of the biologically active natural product diindolylmethane (DIM) with the incorporation of aminophosphonate and urea moieties toward the discovery of potent anticancer agents was considered. A four‐step approach for the synthesis of DIM aminophosphonate and urea derivatives was established. These novel compounds showed potent anticancer activities in two representative kidney and colon cancer cell lines, low toxicity to normal cells, higher potency than the parent natural product DIM and etoposide, and potent inhibition of cancer cell migration. Biophysical and immunological studies, including DAPI nuclear staining, western blot analysis with apoptotic protein markers, flow cytometry, immunocytochemistry, and comet assays of the two most potent compounds revealed good efficacies in apoptosis and DNA damage. It was found that down‐regulation of nuclear factor κB (NF‐κB p65) could be an important mode of action in apoptosis, and the two most potent derivatives were found to be more potent than parent compound DIM in the down‐regulation of NF‐κB. Our results show the importance of structural elaboration of DIM by rational incorporation of aminophosphonate and urea moieties to produce potent anticancer agents; they also suggest that this approach using other structurally simple bioactive natural products as scaffolds holds promise for future drug discovery and development.